(untitled) (Research, Society and Development, 2023)
The number of patients with chronic wounds in the adult community is growing. The presence of these lesions negatively impacts the patient’s lifestyle and well-being, due to the discomfort and pain that make it difficult or completely inhibit the performance of daily activities previously performed by patients. In this scenario, the study aimed to characterize the microbial genera related to the infectious processes of wounds, focusing mainly on the analysis of antimicrobial resistance. The research used qualitative analysis, consisting of three analyses, divided into microbiological collection, inoculation in nutritive medium, Gram stain, inoculation in selective and differential means, biochemical tests and antibiogram. Qualitative analysis of tests and results indicated the presence of Pseudomonas spp and Staphylococcus aureus. The microbial susceptibility test showed a high level of resistance to the tested antimicrobials, in which the analyzed isolates showed an increased resistance to penicillin. The persistence of the lesion and bacterial colonization becomes worrying due to the increase in treatment time and high susceptibility, in addition to the worsening of the clinical and microbiological condition of the patient.